Effects of thyroid hormones on vertebral numbers in two cyprinid fish species: Rutilus rutilus (Linnaeus, 1758) and Abramis brama (Linnaeus, 1758). (2nd March 2018) - Bolotovskiy, A. A.; Levin, B. A.
Summary: Previous studies revealed that thyroid hormones (TH) are crucial regulators of fish development and that manipulation of the thyroid gland function can induce developmental heterochronies. These heterochronies are known to be responsible for changes in the number of serially repeating skeletal elements, such as scales, fin rays and pharyngeal teeth. The present study demonstrates that thyroid function manipulation provokes heterochronies in the development of the fish axial skeleton. We studied the variation of the total vertebral numbers as well as the vertebral numbers in different regions of axial skeleton as influenced by manipulation of level of thyroid hormone in two cyprinid species – the common roach Rutilus rutilus (Linnaeus, 1758) and bream Abramis brama (Linnaeus, 1758). As a result, the numbers of total and caudal (more rarely, abdominal) vertebrae were significantly altered. TH‐treated fish demonstrated a reduced number of vertebrae at an earlier completion of calcification and at a smaller body size. This finding agrees well with the concept of pleomerism sensu C. C. Lindsey (1975 ). Another effect of TH on the phenotype of the axial skeleton was the frequent increase in the number of vertebrae in the caudal skeleton (four in place of the normal three) because of non‐fusions in the urostyle.